Eukaryotic Initiation Factor 5A2 Contributes to the Maintenance of CD133(+) Hepatocellular Carcinoma Cells via the c‐Myc/microRNA‐29b Axis. (20th November 2017) - Bai, Hai‐Yan; Liao, Yi‐Ji; Cai, Mu‐Yan; Ma, Ning‐Fang; Zhang, Qi; Chen, Jie‐Wei; Zhang, Jia‐Xing; Wang, Feng‐Wei; Wang, Chen‐Yuan; Chen, Wen‐Hui; Jin, Xiao‐Han; Xu, Rui‐Hua; et al.
Abstract: Cancer stem cells (CSCs)/cancer‐initiating cells (CICs) are suggested responsible for driving cancer resistance to conventional therapies and for cancer recurrence and/or metastasis. CD133 is served as a key biomarker to identify and characterize this subpopulation of cells in hepatocellular carcinoma (HCC). Our previous study indicated that overexpression of eukaryotic initiation factor 5A2 (EIF5A2) promotes HCC cell metastasis and angiogenesis. In this study, we demonstrated that EIF5A2 might play a crucial role in CSCs regulation and investigated its potential molecular mechanisms. Using quantitative real‐time polymerase chain reaction assay, we observed that the expression of EIF5A2 positively correlated with CD133 levels in a cohort of cancerous and noncancerous liver tissues and cells. Next, HCC cells with high expression of EIF5A2 have a strong capacity to form undifferentiated tumor spheres in vitro and show elevated levels of stem cell‐related genes, leading to an increased ability to develop tumors when subcutaneously injected into nude mice. Furthermore, differential microRNA expression was profiling between two EIF5A2‐depleted HCC cell lines and their control one identified a decreased expression of miR‐29b in EIF5A2‐depleted cell lines. Further functional studies illustrated that downregulated miR‐29b level is responsible for EIF5A2‐maintained HCC cell stemness either in vitro or in vivo. Moreover, enforced expression of EIF5A2 in HCC cells largely enhanced the binding of c‐Myc on the promoter of miR‐29b and downregulation of miR‐29b by EIF5A2 was dependent on c‐Myc. Our findings, collectively, reveal that EIF5A2 contributes to the maintenance of CD133+ HCC cells via the c‐Myc/miR‐29b axis. Stem Cells 2018;36:180–191 Abstract : A schematic model showing the molecular mechanism of eukaryotic initiation factor 5A2 (EIF5A2) regulates CD133 via c‐Myc/miR‐29b pathway in hepatocellular carcinoma cells (HCCs). Upregulation of EIF5A2 enhances the binding of c‐Myc on the promoter of miR‐29b to inhibit its expression, and then upregulating the levels of CD133, thus, HCC cells are prone to maintain their stemness.